2004
DOI: 10.1074/jbc.m406610200
|View full text |Cite
|
Sign up to set email alerts
|

Activation Mechanism of c-Jun Amino-terminal Kinase in the Course of Neural Differentiation of P19 Embryonic Carcinoma Cells

Abstract: P19 embryonic carcinoma cells, a model system for studying early development and differentiation, can differentiate into neurons and primitive endoderm-like cells depending on the culture conditions. We have previously reported that the activation of c-Jun amino-terminal kinase (JNK) is required for the retinoic acidinduced neural differentiation of P19 cells. However, the signaling pathway(s) responsible for the activation of JNK has not been known. In this study, we demonstrated that activities of MAPK kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…These findings are consistent with other reports demonstrating a requirement for the JNK pathway in neurogenesis and NFLC regulation modeled in the distinct in vitro system, P19 EC cells (31). Using these cells, the investigators demonstrate that a TAK1-MKK4-JNK signaling pathway is activated and participates in the regulation of the neural differentiation of P19 embryonal carcinoma cells (2). Also, ES cells in which the JNK pathway-specific scaffold protein, JSAP1, is homozygously disrupted exhibit reduced in vitro neurogenesis (38).…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with other reports demonstrating a requirement for the JNK pathway in neurogenesis and NFLC regulation modeled in the distinct in vitro system, P19 EC cells (31). Using these cells, the investigators demonstrate that a TAK1-MKK4-JNK signaling pathway is activated and participates in the regulation of the neural differentiation of P19 embryonal carcinoma cells (2). Also, ES cells in which the JNK pathway-specific scaffold protein, JSAP1, is homozygously disrupted exhibit reduced in vitro neurogenesis (38).…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that hydrogels enriched with IFN-γ provides suitable substrate for the differentiation of NSCs into neurons (Leipzig et al, 2010). Pro-neuronal differentiation induced by IFN-γ is mediated by the c-Jun N-terminal kinase ( JNK ) pathways (Kim et al, 2007), which is also required for neuronal differentiation of embryonic stem cells and PC12 cells (Wang et al, 2001; Zentrich et al, 2002; Akiyama et al, 2004; Amura et al, 2005). IFN-γ has shown a dual effect on NSCs, because not only stimulates neuronal differentiation, but also promotes migration and reduces proliferation and cell survival of neural progenitors (Ben-Hur et al, 2003; Wong et al, 2004; Song et al, 2005).…”
Section: Cytokines and Nscsmentioning
confidence: 99%
“…Previous studies revealed that JNK was phosphorylated and activated during neural differentiation, 11,12 and that this activation was critical for neurogenesis; 4 however, the mechanism underlying regulation by JNK activation remains unclear. Initially, we tried to evaluate the regulatory activation of JNK in detail.…”
Section: Resultsmentioning
confidence: 97%